Aspirin Protects against Acinar Cells Necrosis in Severe Acute Pancreatitis in Mice. (29th December 2016) - Lu, Guotao; Tong, Zhihui; Ding, Yanbing; Liu, Jinjiao; Pan, Yiyuan; Gao, Lin; Tu, Jianfeng; Wang, Yuhui; Liu, George; Li, Weiqin
Abstract : Aspirin has a clear anti-inflammatory effect and is used as an anti-inflammatory agent for both acute and long-term inflammation. Previous study has indicated that aspirin alleviated acute pancreatitis induced by caerulein in rat. However, the role of aspirin on severe acute pancreatitis (SAP) and the necrosis of pancreatic acinar cell are not yet clear. The aim of this study was to determine the effects of aspirin treatment on a SAP model induced by caerulein combined with Lipopolysaccharide. We found that aspirin reduced serum amylase and lipase levels, decreased the MPO activity, and alleviated the histopathological manifestations of pancreas and pancreatitis-associated lung injury. Proinflammatory cytokines were decreased and the expression of NF- κ B p65 in acinar cell nuclei was suppressed after aspirin treatment. Furthermore, aspirin induced the apoptosis of acinar cells by TUNEL assay, and the expression of Bax and caspase 3 was increased and the expression of Bcl-2 was decreased. Intriguingly, the downregulation of critical necrosis associated proteins RIP1, RIP3, and p-MLKL was observed; what is more, we additionally found that aspirin reduced the COX level of pancreatic tissue. In conclusion, our data showed that aspirin could protect pancreatic acinar cell against necrosis and reduce the severity of SAP. Clinically, aspirin may potentially be a therapeutic intervention for SAP.